Rationalizing the Penn World Table: True Multilateral Indices for International Comparisons of Real Income. - Neary, J (2004)
Real incomes are routinely compared internationally using methods that "correct" for deviations from purchasing power parity. The most widely used of these is the Geary method which, though theoretically suspect, underlies the Penn World Table. This paper provides a theoretical foundation for the Geary method which I call the GAIA ("Geary-Allen International Accounts") system. I show that the Geary method is exact when preferences are non-homothetic Leontief and, more generally, gives a (possibly poor) approximation to the GAIA benchmark. An empirical application suggests that both it and other widely used methods underestimate the degree of international inequality.